Nucleotide sequence and transcriptional start site of the Methylobacterium organophilum XX methanol dehydrogenase structural gene. - Machlin, S M (1988)
The nucleotide sequence of a cloned 2.5-kilobase-pair SmaI fragment containing the methanol dehydrogenase (MDH) structural gene from Methylobacterium organophilum XX was determined. A single open reading frame with a coding capacity of 626 amino acids (molecular weight, 66,000) was identified on one strand, and N-terminal sequencing of purified MDH revealed that 27 of these residues constituted a putative signal peptide. Primer extension mapping of in vivo transcripts indicated that the start of mRNA synthesis was 160 to 170 base pairs upstream of the ATG codon. Northern (RNA) blot analysis further demonstrated that the transcript was 2.1 kilobase pairs in length and therefore appeared to encode only MDH.